The role of corporates in creating sustainable Olympic legacies - Lockstone-Binney, L.; Holmes, Kirsten; Smith, K.; Shipway, R. (Routledge, 2018)
The Olympic Games is a major stimulus for increased tourism. In recent years, there have been greater calls for this and other mega-events to leave sustainable positive legacies for the host city, partly to offset the massive cost of hosting. To date, little consideration has been afforded to the role corporates might play in contributing to event legacies. This gap is compounded by the lack of research examining stakeholder engagement in legacy planning more generally. This paper adopts Holmes, Hughes, Mair and Carlsen’s (2015) sustainable event legacy timeline to conceptualise how corporates through the corporate social responsibility (CSR) initiatives of sponsorship and employee volunteering can engage across the Olympic event planning cycle to generate volunteering legacies. Drawing upon a comparative study of the Sydney 2000 and London 2012 Olympic Games, tentative evidence of corporate engagement was noted but for the most part it was fragmented and CSR initiatives primarily focused on the immediate planning and delivery stages of the event cycle. The paper advances new knowledge of how volunteering legacies can be generated through the best practice engagement of corporates as key stakeholders involved in legacy planning and governance across the Olympic planning cycle.